THE RELATIONSHIP BETWEEN SCAN:3-A AND HEARING-IN-NOISE TEST PERFORMANCES - Velappan, Keerthana (East Carolina University, 2017)
According to the Central Auditory Processing Disorder (CAPD) guidelines by the American Academy of Audiology (AAA; 2010), “specific treatment options (e.g. personal FM systems) may be more appropriately recommended for individuals who present deficits on monaural low-redundancy (MLR) (e.g. speech recognition in noise, filtered or compressed speech) and/or dichotic speech tests.” The assumption appears to be that MLR speech tests may be used to adequately evaluate the necessity for an FM system. In other words, the MLR speech tests may be used to determine the presence of a speech recognition in noise deficit. The purpose of this study was to evaluate the assumption that “low-redundancy” speech tests may be used to identify the need for an FM system by comparing these test results to that of the Hearing-in-Noise Test (HINT; Nilsson et al., 1994; Vermiglio, 2008). Twenty-nine young, native English-speaking with normal pure tone thresholds participated in the study. The subjects were evaluated using the MLR subtests of the SCAN-3:A and the HINT. The SCAN-3:A subtests included: Auditory Figure-Ground (0 dB), Filtered Words, Competing Words-Directed Ear, Competing Sentences, and Time-Compressed Sentences. The standard HINT conditions included; Quiet, Noise Front, Noise Right, and Noise Left. Composite scores were determined for each test battery. Statistically significant relationships were found between most of the SCAN-3:A conditions and HINT conditions. However, while relatively strong relationships between the MLR and HINT test results were found, clinicians should be cautious when inferring the presence of an SRN disorder from the MLR test results.
Keywords: SCAN, speech recognition in noise ability, HINT